The Battle for Guayaquil - Burbano de Lara, Felipe (2009)
In the context of Ecuador’s 2008 Constitutional Referendum, this text analyses the dispute between Rafael Correa –the President of the Ecuadorian government and the figurehead of Alianza País– and the mayor of the largest city in the country, Jaime Nebot. The argument will be developed along three fronts: the battle against neoliberalism, the construction of a national state project, and the search for the political hegemony of Alianza País. The article examines the concepts of autonomy and globalization that were central to Nebot’s discourse and contrasts them with the autonomous model put forward by the government.